2017
DOI: 10.1038/srep43411
|View full text |Cite
|
Sign up to set email alerts
|

Direct mapping of electrical noise sources in molecular wire-based devices

Abstract: We report a noise mapping strategy for the reliable identification and analysis of noise sources in molecular wire junctions. Here, different molecular wires were patterned on a gold substrate, and the current-noise map on the pattern was measured and analyzed, enabling the quantitative study of noise sources in the patterned molecular wires. The frequency spectra of the noise from the molecular wire junctions exhibited characteristic 1/f2 behavior, which was used to identify the electrical signals from molecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
41
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(51 citation statements)
references
References 39 publications
10
41
0
Order By: Relevance
“…The S I / I 2 exhibited a 1/ f noise behavior, as reported in previous noise studies on MoS 2 devices 11 14 . In our previous work, we showed that noise PSDs exhibited 1/ f 2 (or Lorentzian) noise behavior when a current noise was generated by a few trap states that had rather uniform trapping times 15 , 17 . However, noise spectra exhibited 1/ f behavior 15 17 when there were many trap states with various trapping times.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The S I / I 2 exhibited a 1/ f noise behavior, as reported in previous noise studies on MoS 2 devices 11 14 . In our previous work, we showed that noise PSDs exhibited 1/ f 2 (or Lorentzian) noise behavior when a current noise was generated by a few trap states that had rather uniform trapping times 15 , 17 . However, noise spectra exhibited 1/ f behavior 15 17 when there were many trap states with various trapping times.…”
Section: Resultsmentioning
confidence: 99%
“…In our previous work, we showed that noise PSDs exhibited 1/ f 2 (or Lorentzian) noise behavior when a current noise was generated by a few trap states that had rather uniform trapping times 15 , 17 . However, noise spectra exhibited 1/ f behavior 15 17 when there were many trap states with various trapping times. The 1/ f noise behavior in our plot implies that the noise was generated by many different noise sources such as charge traps in the MoS 2 sample.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We now consider the equation of motion for the lesser Green's function which is given by (17). The expansions (18) and (19) are substituted into (17) and, as before, split based on order to give…”
Section: B Non-adiabatic Expansion Of Kadanoff-baym Equations In Wigmentioning
confidence: 99%
“…Another experimental manifestation of the currentinduced forces in molecular junctions is the telegraph noise, which is the stochastic switching over time between two different values of the electric current. Numerous studies of molecular junctions have observed a discrete switching between two or more states in the system, which can be observed via analysis of the measured time-evolution of the current through the system [15][16][17][18]20 . While the exact source of telegraph noise in molecular junctions depends on the particular experimental configuration, it is usually due to either dynamic switching between two different conformations of the molecular bridge or, more often, due to bond fluctuations of the metal-molecule contact.…”
Section: Introductionmentioning
confidence: 99%